An adverse event in a well-established cervical cancer screening program: an observational study of 19,000 females unsubscribed to the program - Larsen MB; Svanholm H; Andersen B (Dove Medical Press, 2016)
Mette Bach Larsen,1 Hans Svanholm,1,2 Berit Andersen1 1Department of Public Health Programmes, 2Department of Pathology, Randers Regional Hospital, Randers, Denmark Introduction: In Denmark, an organized approach to cervical cancer screening has had national coverage since 1998. However, in 2013, it was discovered that 19,000 females had been unsubscribed from the Danish National Cervical Cancer Screening Program and had thus not received invitations or reminders as recommended by the health authorities. The study aims to report the essence of this adverse event and describe the outcomes of reestablishing invitations in terms of participation rates and screening results. Furthermore, patient compensations to affected females diagnosed with cervical cancer and coverage in the mass media was reported.Methods: An observational study based on information from the Danish Pathology Databank, the Department of Public Health Programs, and Infomedia (a Danish database of media coverage) was carried out.Results: A total of 19,106 females were affected. Of those still in the screening age, 37.7% had been tested within 3 years or 5 years despite not receiving any invitation. A total of 21.6% reconfirmed their status as unsubscribed. Of the remaining females, 55.6% were tested within a year, and 94.6% of these test results were normal. Among females aged >64 years, 12.7% accepted the offer of a final screening test. Totally, 90% of these tests were normal. Nineteen females diagnosed with cervical cancer were compensated by the Danish Patient Compensation Association with a total of €693,000, ranging from €8,900 to €239,700. Coverage of cervical cancer screening in the mass media increased from 25 items in the 3 months prior to this adverse event to 590 items in the month when it became public.Conclusion: Even though more than one-third of the affected females were tested despite not receiving regular invitations to participate in the screening program, lacking invitations were ranked alongside other adverse events in the health care system if cancer diagnoses were delayed. Keywords: adverse event, mass screening, uterine cervical neoplasms